Formation of Surface Snow Layer at Mizuho Station, Antarctica - Fujii, Yoshiyuki (1981)
P(論文) On the basis of year round observations of surface snow condition in 1977 and snow stake measurements carried out from 1972 to 1978 at Mizuho Station, which is located at 70°42′S, 44°20′E and 2230m a. s. l. in the katabatic wind region, daily, seasonal and secular changes of surface condition and surface layer formation are studied. The surface level changes gradually by sublimation in summer and condensation in winter, and rapidly by deposition and wind erosion of snow. Surface features change much in the intermediate seasons, when low pressure disturbances is active, between summer and winter. The alternative years variation is seen in the mean annual balance of 202 stakes in 1973-1977,being high in 1973,1975 and 1977 and low in 1974 and 1976. Formation of an annual layer occurs once in two or three years on the average. The mean, maximum and minimum annual balance of 202 stakes in 1973-1977 are 1.5-14.8cm, 36.0-52.1cm and -10.4∿-14.9cm, respectively. The absence of annual layer or layers is mainly due to no deposition of snow and to sublimation of a pre-formed annual layer or layers. A model of transmigration of the surface condition is proposed. departmental bulletin paper